(untitled) (Research, Society and Development, 2023)
Estimates of pediatric cancer by 2022 are 8,500 / year of new cases, which then leads to being considered a public health problem. In addition, cancer treatment can lead to various problems, including fatigue, impacting the quality of life of these patients. Thus, this study aims to correlate fatigue and quality of life in pediatric cancer patients undergoing treatment. A cross-sectional study was carried out, in which 30 patients participated, divided into “outpatient group” and “inpacient group”, according to the place where the data collection was performed. Demographic and clinical data were obtained and two questionnaires were then applied: fatigue (PedsQL ™ Multidimensional Fatigue Scale) and cancer-related quality of life (PedsQL ™ Pediatric Quality of Life ™ Cancer Module). Most of the participants were male and with a mean age of 14 ± 2.89, among the types of cancer presented, leukemia was the most prevalent (43.33%). The inpacient group had more fatigue and less quality of life. life when compared to outpatient, Still, when correlating in general, fatigue has a negative impact on the quality of life of pediatric cancer patients. Therefore, the values presented in this study, point out that fatigue and quality of life are closely linked and that studies are needed in order to develop rehabilitation protocols and, mainly, to create better health conditions and encourage the oncological patient to become functional and independent. with better chances of survival.